Reducing supply chain credit risk - Akinda, Femi (Technical Centre for Agricultural and Rural Cooperation, 2014)
The e-commerce firm SlimTrader has developed a mobile platform called MoBiashara, which aims to reduce supply chain credit risk and promote ‘just-in-time' inventory management.